Subordinasi dan Otonomi Tubuh Perempuan dalam Kumpulan Cerpen L.A Underlover: Feminisme Radikal Kate Millet - Ridwan Ridwan; Nensilianti Nensilianti; Lulyastuti Lulyastuti (SAWERIGADING, 2026)
This study aims to analyse and uncover the forms of subordination of women’s bodies in the short stories Gimbol by Budi Darma and Penafsir Kebahagiaan by Eka Kurniawan, which are governed by patriarchal power, using the perspective of radical feminism developed by Kate Millett. This analysis highlights how women experience subordination in the biological, coercive, economic, mythical, and ideological dimensions of patriarchy. The research method employed is qualitative descriptive, utilising text analysis and meaning interpretation based on the radical feminist theory. The findings reveal that women in these short stories are portrayed as objects of violence and sexual exploitation controlled by the patriarchal system. This analysis affirms the relevance of Millett’s thinking in unravelling the gender inequalities that persist today. The implications of this research suggest that radical feminist analysis can be used to expose practices of gender injustice in literature. These findings also provide insight into patriarchal power relations. AbstrakPenelitian ini bertujuan untuk menganalisis dan mengungkap bentuk-bentuk subordinasi tubuh perempuan dalam cerpen Gimbol karya Budi Darma dan Penafsir Kebahagiaan karya Eka Kurniawan yang dikendalikan oleh kuasa patriarki menggunakan perspektif feminisme radikal yang dikembangkan oleh Kate Millett. Analisis ini menyoroti bagaimana perempuan mengalami subordinasi dalam aspek biologis, paksaan, ekonomi, mitos, dan ideologi patriarki. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik analisis teks dan interpretasi makna berbasis teori feminisme radikal. Hasil penelitian mengidentifikasi bahwa perempuan dalam cerpen-cerpen tersebut digambarkan sebagai objek kekerasan dan eksploitasi seksual yang dikendalikan oleh sistem patriarki. Analisis ini menegaskan relevansi pemikiran Millett dalam membongkar ketimpangan gender yang masih berlangsung hingga kini. Implikasi penelitian ini menunjukkan bahwa analisis feminisme radikal dapat digunakan untuk mengungkap praktik ketidakadilan gender dalam karya sastra. Temuan ini juga memberikan pemahaman tentang relasi kuasa patriarki.